Approximate Solutions of Fractional Riccati Equations Using the Adomian Decomposition Method - Fei Wu; Lan-Lan Huang (Abstract and Applied Analysis)
The fractional derivative equation has extensively appeared in various applied nonlinear problems and methods for finding the model become a popular topic. Very recently, a novel way was proposed by Duan (2010) to calculate the Adomian series which is a crucial step of the Adomian decomposition method. In this paper, it was used to solve some fractional nonlinear differential equations.